Analisis Problematika Guru dalam Pembelajaran Daring pada Pembelajaran Tematik di SD/MI - Nila Nila; Lathifah Abdiyah; Agus Dwi Prasojo (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to explain the problems of online learning for teachers in improving thematic learning in SD/MI during online learning. The research method used in this study is  a  qualitative  research  method.  Based  on  the  object of study, this research is a literary research or library research. Library research is a research conducted by collecting data, information,  and  various other data contained in the library. Sources of  data  used  in  this  study  are  books, journals, articles, and other scientific works that  are  relevant  to  the  object  of study in this study. The results of  the study show that  the problems     of online learning have an impact on teachers and explain online learning in thematic learning and its problems.